Impact of antecedent factors on collaborative technologies usage among academic researchers in Malaysian research universities / Halimi Zakaria - Zakaria, Halimi (Institute of Graduate Studies, UiTM, 2016)
Research collaboration through the use of collaborative technologies has the huge potential to improve research publication performance. In order to ascertain optimal usage of collaborative technologies in Malaysian research universities, the main objective of this study is therefore to investigate significant antecedents or drivers to usage of collaborative technologies. The research objectives addressed by this study include (a) the investigation of the relationships between each of these antecedent factors of personal innovativeness in IT, task-technology fit, perceived management support, subjective norm and perceived peer usage with perceived usefulness and individual usage; and (b) the investigation of the relationship between perceived usefulness and individual usage of collaborative technologies for research collaborations. Renowned technology acceptance theories and models, namely the Technology Acceptance Model (TAM) (Davis, Bagozzi & Warshaw, 1989), the Theory of Planned Behavior (Ajzen, 1985; Ajzen, 1991), the Task-Technology-Fit model (TTF) (Goodhue & Thompson, 1995) and the Technology-Organization-Environment (TOE) model (Tornatzky & Fleischer, 1990; Zhu & Kraemer, 2005) were used to form the broad hybridized research model of this study. The research model assessed the antecedents of collaborative technologies usage by looking at three critical contexts of technological, organizational, and social perspectives. The model also investigates the mediating effect of perceived usefulness on individual usage…